Efektivitas Penyuluhan Terhadap Perilaku Deteksi Dini Kanker Leher Rahim Metode Tes IVA Pada WUS di Puskesmas Pembantu Muaratais Tahun 2019 - Daulay, Suryani Agustina; Sitorus, Samsidar; Sibero, Jitasari Taringan (Jurnal Kesehatan Ilmiah Aufa Royhan, 2019)
Cancer is the second leading cause of death in the world (13%) after cardiovascular disease. Cervical cancer is the most common cancer in women with 7.5% of all deaths. The purpose of this study was to determine and analyze the effectiveness of counseling on the early detection of cervical cancer IVA method in WUS at the Muaratais Helper Health Center in 2019. This type of research is a Quasi experimental study. The population in this study was WUS mothers in the Working Area of Muaratais Support Health Center as many as 1390 people. The sample consisted of 60 WUS mothers. The sample was divided into 2 groups: the Experiment and Control group with 30 people each. The experimental group was intervened with counseling and the control group was not given an intervention. The instrument used was a questionnaire. Data analysis was performed univariate, bivariate. The results showed in the experimental group after being given counseling the results of paired statistical t test with a significant level of sig α 0.05 obtained p-value 0,000 <0.05, which means there are differences before counseling and after counseling on knowledge about early detection of cancer cervix IVA method on WUS at the Muaratais Support Health Center in 2019. The conclusion of this study is that counseling is effective in improving maternal behavior in early detection of cervical cancer IVA test methods.